Comprehensive Echocardiographic Assessment of the Right Ventricular Performance: beyond TAPSE and Fractional Area Change - E. Surkova; A. Kovács (Российский кардиологический журнал)
Right ventricular (RV) performance is an important predictor of adverse events and mortality in patients with cardiovascular diseases. Echocardiography is the first-choice imaging modality for the assessment of RV systolic function, however conventional two-dimensional echocardiographic parameters have important limitations and under specific conditions poorly correlate with the gold-standard imaging modality, cardiac magnetic resonance. Recent advances in novel echocardiography techniques, including three-dimensional echocardiography and two-dimensional speckle-tracking echocardiography opened new era in RV imaging enabling more accurate and reproducible assessment of RV performance thus providing deeper insight into the pathophysiology of this intriguing cardiac chamber. In this comprehensive review authors summarize the state-of-the-art echocardiographic approach to the assessment of the RV systolic function with specific emphasis on modern techniques, their advantages, limitations and pitfalls in the various clinical settings.